Genomic Attributes of Novel Symbiont Pseudovibrio brasiliensis sp. nov. Isolated From the Sponge Arenosclera brasiliensis - Fróes, Adriana M.; Freitas, Thamyres C.; Vidal, Livia; Appolinario, Luciana R.; Leomil, Luciana; Venas, Tainá; Campeão, Mariana E.; Silva, Carlos J. F.; Moreira, Ana Paula B.; Berlinck, Roberto G. S.; Thompson, Fabiano L.; Thompson, Cristiane C. (Frontiers in Marine Science, 2018)
Sponge holobionts are defined as the host animals and their associated microbiomes. Both host and microbiome produce extracellular products that facilitate interaction within the holobiont. For example, microbes may provide nutrition for the animal host and protection against pathogens. The genomic study of bacterial cultures may shed light on the properties of novel symbiotic bacteria isolated from marine holobionts. In this study, we performed a genome-based analysis of Pseudovibrio brasiliensis Ab134T isolated from the sponge Arenosclera brasiliensis. This novel strain is phylogenetically related to Pseudovibrio denitrificans. In silico DNA-DNA hybridization and calculation of the average amino acid identity between the strain Ab134T and P. denitrificans JCM 12308T showed <70% similarity and <95% identity, respectively. This novel bacterial species possesses genomic features that hint at several possible roles in symbiosis (e.g., production of secondary metabolites, including bromotyrosine-derived alkaloids) in sponge and coral holobionts. We also detected gene clusters encoding type III, type IV, and type VI secretion systems and 26 toxin-like proteins, including probable paralogs. Our results demonstrate the genome versatility of P. brasiliensis Ab134T and the potential to attach to host cells, which may play a role in its symbiotic lifestyle.